Uprość wyrażenia. :
a) 5 * (xy)
b) 3a/4 * (- 2a/3)
c) - 2x * (- 3xy)
d) x - x/2 - x/3
e) - 4 * (- x/2) * (- 2x/4)
f) x+1/2 + 2x-1/4
g) - (x+1) + (2x + 4)
h) 3 (a do kwadratu - 4) - (a do kwadratu + 2)



Bardzo proszę o szybką odpowiedź:)


Odpowiedź :

a) 5xy
b)-a/2
c) 6x do kwadratu * y
d) x/6
e) - x do kwadratu
f) 3x - 1/4
g) x + 3
h)2a do kwadratu - 14
a) 5 * (xy)=5xy
b)) 3a/4 * (- 2a/3)=-a²/2
c)- 2x * (- 3xy)= 6x ²* y
d) x - x/2 - x/3=6x/6 -3x/6-2x/3=
x/6
e)- 4 * (- x/2) * (- 2x/4)= - x²
f) x+1/2 + 2x-1/4= 3x+2/4-1/4=3x - 1/4
g)- (x+1) + (2x + 4)=-x-1+2x+4= x + 3
h)3 (a do kwadratu - 4) - (a do kwadratu + 2)=2a ²- 14